Principal Participatory Leadership Management in Improving Teacher Performance - Zega, Novelina; Sitanggang, Nathanael; Nasrun (Jurnal Pendidikan Indonesia, 2022)
Currently, efforts to improve teacher performance in Indonesia are urgently needed. The low performance of teachers is an indication of the low ability of the principal in carrying out his role as an educational leader. As a result, this condition not only affects teachers but also students. The potential of students is not explored and developed optimally. This study aims to analyze the relationship of participatory leadership on teacher performance. The sample in this research was high school teachers, totaling 50 people. This study used questionnaires as primary data and then the results of the data were analyzed using simple linear regression with the help of the SPSS 26 tool. The results of this study were that there was a positive and significant relationship between participatory leadership and teacher performance as seen through simultaneous test results with Fcount of 58.232 and a probability value or p value = 0.000 less than 0.05. The results of the partial test show that participatory leadership has a positive and significant effect of 0.000 and tcount of 7.631. So it can be concluded that there is a positive relationship between the principal's participatory leadership on teacher performance. So it is necessary to have another leadership style that can improve teacher performance in carrying out their duties as educators in learning activities.